The Implementation of Literacy Activities in Primary School - Prawira, Ni Nyoman Pradnyani; Artini, Luh Putu; Marsakawati, Ni Putu Era; Padmadewi , Ni Nyoman; Ratminingsih , Ni Made; Utami, I G A Lokita Purnamika (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
School Literacy Movement is a program which has been voiced by the Indonesian Minister of Education and Culture since 2015. This program aimed to promote and support reading culture in school due to consistent unsatisfactory result of Program of International Student Assessment indicate the need for special effort to improve the young generation’s literacy skills.  This study aimed at analyzing such efforts in the school level. The study employed a qualitative research design which explored the types of literacy activities implemented in the school to support literacy movement program. Classroom observation and interview were conducted to collect the data from Bali Kiddy School. There were 2 teachers who gave their consent to be involved in this study. The data were analyzed descriptively. These phases include categorizing the data, presenting the findings, and evaluating and validating the data. The finding reveals that the schools have some strategies to engage students to read non-subject books, write reading response journal, do spelling and writing activities. To encourage children's literacy development, building a literacy environment where they are highly exposed to the language is essential.